Exploring the Financial Health of Municipalities in Nepal - Sharma, Devilal; Paudel, Resam Lal; Yadav, Umesh Singh; G C, Surya Bahadur; Tiwari, Indra Prasad; Thapa, Ajay (Journal of Political Science, 2025)
This study examines financial distress faced by Nepalese municipalities and explores strategies for reducing financial risk to promote community development. Focus group discussions (FGDs) were conducted in Pokhara, Biratnagar, and Dhangadi as part of a qualitative research approach. Each group comprises eight to twelve participants. To ensure sustainable fiscal health, the study emphasizes the importance of enhancing capacity-building initiatives, diversifying sources of revenue, revising investment-related legislative frameworks, and improving tax collection. It also highlights the need for central and provincial policy changes to provide local governments to empower the local government with more control over their finances and governance. The study examines municipalities' financial circumstances and provides solutions for improving fiscal effectiveness and promoting the socioeconomic growth of municipalities in Nepal. Finally, the provincial and central governments must comprehensively reform policies to grant more autonomy to the local government in both governance and financial management practices to strengthen the fiscal health of urban municipalities in Nepal, supporting their contribution to the broader socio-economic development of the country.